Incorporating nutritional goals into international agricultural research - an ILCA perspective - Gryseels, Guido; Whalen, I.T. (International Food Policy Research Institute, 1984)
Outlines the activities and programs of ILCA that affect the nutritional status of the underfed human population; discusses the linkage between livestock production & human nutriton, commodity priorities & characteristics and alternative choices for nutritional improvement; ends with suggestions for strengthening nutritional concerns in ILCA research.